Energy consumption and economic growth in ASEAN. - Siti Raudah Hamzah. (2010)
This study investigates the causal relationship between energy consumption and economic growth and electricity consumption and economic growth in the Association of South East Asian Nations (ASEAN) covering 5 countries (Indonesia, Malaysia, The Philippines, Singapore, and Thailand). Throughout the study, time series data from 1980 to 2006 was applied to investigate two relationships. The techniques of Standard Granger Causality, Error Correction Model and the Hsiao’s Final prediction error rule (FPE) had been applied to make clear of the causality relationship between the variables. The empirical studies strongly indicated that the causal relationship among the variables is not uniform across all the 5 ASEAN countries. Bi-directional causality between electricity consumption and economic growth existed for Malaysia, The Philippines, Singapore and Thailand while bidirectional causality between energy consumption and economic growth for Singapore, The Philippines and Malaysia were found. Also, unidirectional causality from energy consumption to economic growth was found for Indonesia. We strengthened the analysis by making comparisons with other similar studies. Differences in the comparison of the results can be accounted for by the diverse conditions (time lags, nature of the data, and application of different tests) which have significant impact on the results.